MODEL PENDIDIKAN ISLAM DENGAN PENDEKATAN HUMANISME RELIGIUS (Studi Kasus di MTs Attanwir Talun Sumberrejo, Bojonegoro) - Hamam Burhanuddin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Education is a conscious and deliberate effort between educators (teachers) with the learners in order to achieve a goal, one of the ideal goal of education is the education that liberates and no curb. Expected model of Islamic education with religious humanism approach this teaching process is not bound by space and time, in the sense of teaching can occur anywhere during the learners have a strong interest in understanding and developing the subject matter. How learning model that is able to synergize the interest and motivation that is the duty of the teacher to the learner in the learning process, in the classroom and outside the classroom. The model is a mix of religious humanist approach humanist education paradigms and paradigm of religious education which is integrated into a coherent whole. Humanist education that emphasizes individual liberty aspects are integrated with religious education in order to build individual and social life which have independence, leaving no religious values followed by community